2021
DOI: 10.3390/met11020255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heat Treatment Parameters on Microstructure and Hardness Properties of High-Speed Selective Laser Melted Ti6Al4V

Abstract: This study presents the investigation on how heat treatment parameters, which are temperature, cooling method, and residence time, influence the microstructural and hardness properties of Ti6Al4V components produced on Ti6Al4V substrate using high speed selective laser melting technique. Heat treatment was performed on the produced samples before they were characterized for microstructure and hardness. The microstructure of the as-built sample contained large columnar β-grains that were filled with martensite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…The as-built L-PBF-ed Ti6Al4V alloy shows a fully or majority martensitic (α′) microstructure within prior columnar β-grains that are arranged along the build direction ( Figure 32 a,b,d,f), as also reported by [ 32 , 59 , 211 , 212 ].…”
Section: L-pbfed Ti6al4v: Microstructuresupporting
confidence: 80%
See 4 more Smart Citations
“…The as-built L-PBF-ed Ti6Al4V alloy shows a fully or majority martensitic (α′) microstructure within prior columnar β-grains that are arranged along the build direction ( Figure 32 a,b,d,f), as also reported by [ 32 , 59 , 211 , 212 ].…”
Section: L-pbfed Ti6al4v: Microstructuresupporting
confidence: 80%
“…As previously reported, the other focal point is the cooling method; however, in this case, it also depends on the temperature from which the cooling pathway starts. The effects induced by the cooling rate are moderate if the samples are heat-treated in low-SSTRs, but they become very important when the samples are at temperature > T 0 , as previously discussed [ 32 , 212 , 265 , 271 , 276 , 285 ]. Focusing on this last temperature range, Etesami et al [ 285 ] reported a microstructure formed by primary α-phase containing β-particles and needle-like α′-martensite after 930 °C × 2 h (WQ).…”
Section: L-pbfed Ti6al4v: Microstructurementioning
confidence: 75%
See 3 more Smart Citations